Role of anti-CD40 antibody-mediated costimulation blockade on non-Gal antibod production and heterotopic cardiac xenograft survival in a GTKO.hCD46Tg pig-to-baboon model - Mohiuddin, Muhammad M. (Xenotransplantation, 2013)
BACKGROUND: Recently, we have shown that an immunosuppression regimen including costimulation blockade via anti-CD154 antibody significantly prolongs the cardiac xenograft survival in a GTKO.hCD46Tg pig-to-baboon heterotopic xenotransplantation model. Unfortunately, many coagulation disorders were observed with the use of anti-CD154 antibody, and recipient survival was markedly reduced by these complications. MATERIAL AND METHODS: In this experiment, we replaced anti-CD154 antibody with a more clinically acceptable anti-CD40 antibody while keeping the rest of the immunosuppressive regimen and the donor pig genetics the same. This was carried out to evaluate the antibody's role in xenograft survival and prevention of coagulopathies. Two available clones of anti-CD40 antibody were tested. One mouse anti-human CD40 antibody, (clone 3A8), activated B lymphocytes in vitro and only modestly suppressed antibody production in vivo. Whereas a recombinant mouse non-human primate chimeric raised against macaque CD40, (clone 2C10R4), blocked B-cell activation in vitro and completely blocked antibody production in vivo. RESULTS: The thrombotic complications seen with anti-CD154 antibody were effectively avoided but the graft survival, although extended, was not as prolonged as observed with anti-CD154 antibody treatment. The longest survival for the 3A8 antibody group was 27 days, and the longest graft survival in the 2C10R4 antibody group was 146 days. All of the grafts except two rejected and were explanted. Only two recipient baboons had to be euthanized due to unrelated complications, and the rest of the baboons remained healthy throughout the graft survival period or after graft explantation. In contrast to our anti-CD 154 antibody-treated baboons, the non-Gal antibody levels started to rise after B cells made their appearance around 8 weeks post-transplantation. CONCLUSIONS: Anti-CD40 antibody at the current dose does not induce any coagulopathies but while effective, had reduced efficacy to induce similar long-term graft survival as with anti-CD154 antibody perhaps due to ineffective control of B-cell function and antibody production at the present dose. More experiments are required to determine antibody affinity and effective dose for inducing long-term cardiac xenograft survival.